Soils and Fertilizers for Master Gardeners: Tackling Soil Salinity Problems in the Home Landscape - Amy L. Shober (EDIS, 2008)
SL-262, a 3-page fact sheet by Amy L. Shober, provides information about diagnosing and dealing with salinity problems in the home landscape or garden. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Sciences, July 2008.